Monday

December 22, 2014

December 22, 2014

Posted by **plz help** on Friday, May 4, 2012 at 9:11am.

f(0)=

f(-1)=

f(2)=

- math -
**Bosnian**, Friday, May 4, 2012 at 10:15amf ( 0 ) = 3 * 0 ^ 2 - 4 * 0 = 3 * 0 + 0 = 0 + 0 = 0

f ( - 1 ) = 3 * ( - 1 ) ^ 2 - 4 * ( - 1 ) = 3 * 1 + 4 = 3 + 4 = 7

f ( 2 ) = 3 * 2 ^ 2 - 4 * 2 = 3 * 4 - 4 * 2 = 12 - 8 = 4

**Answer this Question**

**Related Questions**

Math - Find the indicated outputs for f(x)=5x^2-2x. f(0)= f(-1)= f(2)=

Math - Find the indicated outputs for f(x)= 5x^2-5x. F(0) = 0 f(-1)= 1 f(2)= 45 ...

math - Function k(x) = x+18 Find k(0) k(x) = 6x k(-2) k(5) k(-2) indicated ...

Math - Find the indicated outputs for f(x)= 5x^2-2x The 2 after the ^ is an ...

math - can someone help me I am not understandng how to do this; Function k(x...

math - can someone check this please find indicated outputs for f(x)= 4x^2 - 2x ...

Algebra - Find the indicated outputs for f(x)=¡¼5x¡½^(2 )-2x f(0)= f(-1)= f(2)=

algebra - Find the indicated outputs for f(x) =4x^2 -4x f(0) f(-1) f(2)

algebra - Find the indicated outputs for f(x)=4x^2 -4x f(0) f(-1) f(2)

algebra - find the indicated outputs for f(x)5^2-4x F(0)= f(-1)= f(2)=